Racial Antagonism, Sexual Betrayal, Graft, and More: Rethinking and Remedying the Universe of Defense Counsel Failings - Sheri Lynn Johnson (Washington University Law Review, 2019)
What should happen if a lawyer sleeps during parts of the trial—or is sleeping with the prosecutor? If defense counsel was mentally ill or intoxicated during the trial, should a court measure her performance by the deferential standards that apply to most ineffective assistance of counsel claims? Or should that court, after ascertaining those facts, simply grant the defendant a new trial? What about defendants represented by lawyers who aim to profit by securing media rights to their client’s case? Or defendants represented by lawyers seeking employment with the district attorney’s office? No one doubts that lawyers should refrain from the use of racial slurs, from sleeping during trial, from “sleeping with the enemy,” from representing clients while mentally ill, from intoxication in the courtroom, or from securing illicit gains through the travails of their clients. Such prohibitions are generally imposed by rules of professional ethics, but those rules do not address the consequences for the criminal defendant whose lawyer ignored them. Cases raising these and similar questions are rife in the lower courts. To date, the Supreme Court has not considered the appropriate remedies for any of these transgressions. Its precedents do, however, establish three categories of counsel failure, each with a different standard for judging whether the failure harmed the defendant enough to demand a new trial: the truant, the torn, and the terrible. Under claims governed by United States v. Cronic, a defendant who proves that his lawyer was “truant,” that is, absent or constructively absent, need show no more. This is the most defendant friendly, but least common, category. A slightly larger category, defendants with “torn” lawyers, must, pursuant to Cuyler v. Sullivan, show the existence of a conflict of interest, and show that the existing conflict “adversely affected” the lawyer’s performance. But by far the largest category of counsel failure claims, those involving present, presumptively loyal, but just plain terrible lawyers, are governed by the harsh standard of Strickland v. Washington, which requires proof that trial counsel was incompetent, and proof of “prejudice”—a “reasonable likelihood” that competent representation would have resulted in a different verdict. This article aims to rethink the categories of counsel failure; no article to date does so.
Keywords: Sixth Amendment; Criminal defense; Criminal law; Constitutional law; United States v. Cronic 466 U.S. 648 (1984); Cuyler v. Sullivan 446 U.S. 335 (1980)